Um olhar: o favelário nacional - Leandro Praes Xavier da Silva (2023)
This text refers to an intellectual line that thought and debated the questions of national conformation from the perspective of popular life. Here we outline, through contributions not only from geographical field, the themes of poverty, the initial problems of brazilian urbanization, the critical theory about national formation, the work category (de)formation in Brazil, and, meanly, Roberto Schwarz’s point of view around past and present of these matters. The way we thought leads for the original duality of national formation in brazilian modernization. It’s understood that favela is a one more moment manifestation that don’t stall in binary immobility. We indicate the demonstration that dialectical thought, despite it often functions in two poles, does not stay necessarily on bad dualism, but is the very movement of national particularity.